Educação Física escolar em tempos de pandemia: principais desafios dos professores e alunos durante o ensino remoto - Machado, Raissa da Silva (Brasil, 2023)
The present work is characterized as a literature review, where it was based on reports of published experiences, on school physical education in times of the COVID-19 pandemic. Its objective was to verify in the literature the sharing of reflections, by teachers, on remote teaching in Physical Education classes at school, to understand the difficulties faced by teachers and students in relation to information technologies, the long workday and the lack of of financial, pedagogical and emotional support, thus exposing the strategies used by them in face of their reality. Likewise, an attempt was made to find out which actions were carried out by Public Policies, in a Federal, State and Municipal position to remedy the existing problems in education in this period. The research was carried out in databases such as Scielo, Google Scholar and Periodicals Capes/CAFE. The results of the research showed that, despite several government actions taken to reduce the impact of teaching, the difficulties of adapting to the media and digital/technological exclusions are still very present. In view of the above, the brief question remains about the other solutions that could be carried out in this pandemic period and what are the plans for future teaching.